(untitled) (Innovaciones Educativas, 2021)
The COVID-19 health emergency has thwarted many of the educational systems worldwide. As a result, some of the gaps and inequalities in Ibero-America became evident, with important challenges related to the quality and equity of education. Firstly, the most immediate need is to promote strategies for the return and recovery of educational processes, with a particular focal point on the most vulnerable groups who have been most affected during this period. We must bet on a profound transformation of the system in the long term. It is about taking advantage of this crisis to review the educational model promoting learning throughout life and for all. Advancing in this task requires proposals supported by public policies built in cooperation and inter-institutional collaboration along with strategies for institutional strengthening and capacity development.